THE EFFECT OF READING INTEREST ON READING COPREHENSION OF GRADE XII HIGH SCHOOL STUDENTS OF SMA NEGERI 1 BRANDAN BARAT - Khadijah; Pasaribu, Arsen Nahum (Unversitas Katolik Santo Thomas, 2022)
ABSTRACT This study aims to find out the effect of reading interest on the reading comprehension of grade XII high school students of SMA Negeri 1 Brandan Barat. This is an ex-post-facto study using a mixed-method approach and quantitative and qualitative data. The population of this study was 180 12th grade students of SMA Negeri 1 Brandan Barat for the 2020–2021 academic year majoring in social sciences (IPS) and natural sciences (IPA). The procedure of sampling taking for this study was a randomly selected sampling plan. Slovin’s formula was used to compute the samples. The computed sample size was 64 students from a population of 180 students. The data collection methods used were the questionnaire method and a test of reading comprehension. The data collected was analyzed using multiple linear regression analysis with partial test hypothesis testing (t-test). The findings of this study indicated that the t-value = 6,201 > t-table 1,669 with a significance value of 0.000 0.05, then Ha was accepted. This shows that partially Ha, which stated that there was an effect of reading interest on reading comprehension, is accepted. It can be concluded that reading interest affected the reading comprehension of Grade XII high school students of SMA Negeri 1 Brandan Barat.